Методи та НВІС-структури пристроїв паралельно-вертикального обчислення сум парних добутків - Цмоць, І.Г.; Балич, Б.І.; Скорохода, О.В. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
VLSI-oriented methods and structures of parallel-vertical calculations of even products sums have been developed. Valuations of hardware expenditure and developed structures performance have been carried out.